2013
DOI: 10.1016/j.ijcard.2012.03.072
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic androgenic steroid use is associated with ventricular dysfunction on cardiac MRI in strength trained athletes

Abstract: Strength athletes who use AAS show significantly different cardiac dimensions and biventricular systolic dysfunction and impaired ventricular inflow as compared to non-athletes and non-AAS-using strength athletes. Increased ventricular volume and mass did not exceed that of strength-endurance athletes. These findings may help raise awareness of the consequences of AAS use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 46 publications
(55 reference statements)
1
30
0
6
Order By: Relevance
“…These observations are further supported by studies which have failed to demonstrate significant concentric cardiac remodeling with prospective resistance training regimes (Spence et al 2011;Utomi et al 2014;Haykowsky and Tomczak 2014). It may be that the apparent contradiction in studies between the presence and extent of cardiac remodeling in strength trained athletes may be explained by confounding influences such as the use of anabolic steroids (Luijkx et al 2013).…”
Section: Discussionmentioning
confidence: 74%
“…These observations are further supported by studies which have failed to demonstrate significant concentric cardiac remodeling with prospective resistance training regimes (Spence et al 2011;Utomi et al 2014;Haykowsky and Tomczak 2014). It may be that the apparent contradiction in studies between the presence and extent of cardiac remodeling in strength trained athletes may be explained by confounding influences such as the use of anabolic steroids (Luijkx et al 2013).…”
Section: Discussionmentioning
confidence: 74%
“…Significantly, multiple recent controlled studies which used cardiac magnetic resonance imaging (Luijkx et al . ) or cardiography (Hassan et al . , Montisci et al .…”
Section: Resultsmentioning
confidence: 99%
“…It has confirmed that use of AAS may lead to cardiac hypertrophy and has hypothesized a direct cardiotropic effect [15] associated with a significantly lower left ventricle ejection fraction and decreased diastolic function [16] strongly associated with mean dosage and duration [17,18]. Furthermore, some recent innovative diagnostic techniques, such as pulsed-wave tissue Doppler imaging and ultrasonic-integrated backscatter cyclic variation analysis [19] and cardiac magnetic resonance (CMR) [20], documented regional systolic and diastolic dysfunction in AAS users with respect to AAS non-users or control cases. Angell and colleagues [21] could detect pathological alterations of ventricular structure and dysfunction in the hearts of AAS users in CMR analyses.…”
Section: Discussionmentioning
confidence: 98%